Principal Factors Defining Success of Technical-Tactical Actions of Elite Football Team (Baltic Journal of Sport and Health Sciences, 2014)
Research background and hypothesis. Factor analysis method enables to reveal the complex of dominating indicators determining the competitive result, as well as to define extend of interrelation between indicators and establish the role of individual factors important in the achievement of sports result.  The aim of this study was to reveal manifestations of factors of technical-tactical actions determining success of football teams taking part in the country’s championship.Research methods. The study participants were 24 football players from elite level “Aktobe” team, playing in Kazakhstan Premier League and the champion of Kazakhstan. The technical-tactical actions was analysed separately and compared during the first and the second rounds of the championship (1 1 games in each round). Research results. The analysis of factor contribution into the structure of technical-tactical actions in the first and the second rounds of the country’s championship showed that during the second round of the championship the volume of technical-tactical actions, indicating the possession of play initiative, decreased from 49.6 to 44.1% of total variance, but the contribution of technical-tactical actions, indicating completing of team’s attacking actions, increased from 16.5 up to 24.8% of total variance. It enabled the team to score more goals in the second round of the championship. Discussion  and  conclusions.  Pursuant  to  the  factor  analysis,  such  indicators  as  “short  and  medium  passes forward”, “long passes”, “interceptions”, “hitting the goals” and “total number of technical-tactical actions” are dominating parts of the integral factor – “Possession of play initiative”. Quantifying all the activities of individuals, group of players and of the entire team, which contributed to achievement of elite football teams, is essential in programming and managing the training process.Keywords: football, game analysis, technical and tactical preparation.